Development and initial validation of an electronic personal assessment questionnaire for menstrual, pelvic pain and gynaecological hormonal disorders (ePAQ-MPH). (July 2019) - Gray, Thomas G.; Moores, Karen L.; James, Ellie; Connor, Mary E.; Jones, Georgina L.; Radley, Stephen C.
Abstract: Objective: Menstrual disorders, pelvic-pain and gynaecological hormonal conditions in women can have a significant impact on quality-of-life. Reliable assessment and monitoring of these intimate conditions is challenging. Patient reported outcome measures (PROMs) can be invaluable in providing objective assessment, but no comprehensive PROM assessing all of these conditions and their impact on quality of life is currently available. The purpose of this study was to develop and undertake initial psychometric testing of a comprehensive interactive electronic patient reported outcome measure for these conditions. Study design: A prototype electronic PROM (ePAQ-MPH) was developed following systematic literature review, semi structured interviews with 25 patients and expert panel review. Exploratory factor analysis was undertaken in 291 women attending a menstrual-disorders clinic; establishing a domain structure and enabling item reduction. Two validated PROMS (Women's Health Questionnaire and Menstrual Distress Questionnaire) were completed to assess criterion validity in 213 patients. Test-retest reliability was carried out in 30 women completing ePAQ-MPH at least one week apart. Patients' views on 'Value' and 'Burden' were assessed in 278 women using a validated 10-item survey measuring questionnaire utility (QQ-10). Confirmatory factor analysis (CFA) of the revised version of ePAQ-MPH following item reduction was undertaken in a different sample of 254 women. Results: Exploratory factor analysis identified 18 domains (Cronbach's α > 0.7) and 30 redundant items. Test-retest analysis found acceptable intra-class correlations of 0.6–0.9 ( p < 0.05). Eight domains were compared with Menstrual Distress Questionnaire showing moderate or strong correlation in seven domains. Ten domains were compared with Women's Health Questionnaire, six of which showed moderate correlation. Mean QQ-10 Value and Burden scores were 76 and 25, respectively (SD=15.8 and 15.5). The mean completion time for ePAQ-MPH was 31 min. CFA of the revised version 2 instrument with 15 domains showed good model fit. Conclusions: Whilst wider psychometric testing of the revised version of ePAQ-MPH is required, including in different settings and in assessments of data quality and responsiveness, initial analysis provides some evidence for reliability, validity and acceptability of this multi-dimensional electronic PROM. ePAQ-MPH shows potential for both patient assessment and roles in service evaluation and research.